RESEPSI AKTIVIS ROHANI ISLAM TERHADAP BACAAN KEAGAMAAN DI SMAN 1 DAN 3 BANDA ACEH: ROHIS ACTIVISTS’ RECEPTION OF RELIGIOUS READING MATERIALS: A CASE STUDY IN SENIOR HIGH SCHOOLS 1 AND 3 IN BANDA ACEH, ACEH PROVINCE - Muhammad Tarobin (Penamas, 2014)
Recent research publications demonstrate that some school students as well as their religious teachers tend to support ideas that have been promoted by radical Islamic organizations. They also give their support to some acts of religious violence. Given these publications, it is important to see whether this radical tendency among school students is affected by religious reading materials which those students read. Using the framework of media reception theory, this research examines religious reading materials read by ROHIS activist students and their reception of those materials. ROHIS (Rohani Islam) is one of the religious extra-curricular activities at schools. The study was conducted in Senior High Schools 1 and 3 in the city of Banda Aceh, Aceh Province. The author found that in these two schools ROHIS activists tended to selectively read religious reading materials according to their religious tradition and religious motivation as well as the styles of language and writing of the materials they read. Key Words: Religious reading materials, ROHIS activists, Banda Aceh. Beberapa hasil penelitian menunjukkan, bahwa beberapa siswa sekolah dan guru agamanya lebih mendukung ide-ide gerakan Islam radikal. Mereka juga mendukung aktifitas kekerasan atas nama agama. Hal ini menjadikan penting untuk melihat apakah kecenderungan terhadap radikalisme di kalangan siswa tersebut dipengaruhi oleh bahan bacaan yang mereka baca. Dengan menggunakan kerangka teori resepsi media, penelitian ini menjelaskan bahan bacaan keagamaan dan resepsi (penerimaan/tanggapan) siswa terhadap bahan bacaan tersebut. Rohis (Rohani Islam) adalah salah satu kegiatan ekstrakurikuler keagamaan di sekolah. Penelitian dilakukan di SMAN 1 dan 3 Kota Banda Aceh. Peneliti menemukan, bahwa Rohis SMAN 1 dan 3 Kota Banda Aceh lebih memilah secara selektif buku-buku keagamaan tertentu berdasarkan ikatan tradisinya, motivasi beragama, dan gaya bahasa dan penyampaian. Kata Kunci: Rohis, bacaan keagamaan, Aceh.